Sovereignism is served: Salvini’s rhetoric of the good made in Italy - Terracciano, Bianca (E|C, 2020)
This contribution is the result of a semiotic analysis of Matteo Salvini's speeches and social media practices, which took place over the period 2012-2019. It was decided to focus attention on the gastronomic posts published on Instagram, the reference social network for the publication of images which, together with Facebook and Twitter, is configured as a widespread opinion channel, often subservient to punctual, evanescent and momentary passions . Salvini photographs and exalts only genuine foods because they are Italian, an axiology that is intentionally extended, by way of a semantic halo, to the isotopies of his politics, that can be found in the verbal texts published in the form of captions. Generally these are "national-popular" utterances relating to the safeguarding of the Italian heritage. Furthermore, the dishes rise to figures of the discursive configurations of his political program, such as the bulldozer-shaped cake or the mixed fried food, a metaphor for ethnic and cultural mixing.